The Geomorphological Map of the Northern Foothills, Terra Nova Bay (Antarctica) - BARONI, CARLO; SALVATORE, MARIA CRISTINA; BONDESAN A.; MENEGHEL M.; OROMBELLI G. (Australian and New Zealand Geomorphology Group and International Association of Geomorphologists, 2009)
The Geomorphological Map at scale 1:50.000 includes the Northern Foothills which are located along theTerra Nova Bay coastal stretch, where the Italian Antarctic Station was established, the Hells Gate Ice Shelf (HGIS), which may be considered part of the Nansen Ice Sheet, and the Inexpressible Island. The map is based on field research carried out during several Italian Antarctic Expeditions and on photointerpretation of aerial photographs (1956-57 and 1985). Geomorphological symbols are organized in the following subsets: 1- areal distribution of ice types (snow and firn, continental glacier ice, marine ice, first-year ice, multi-year landfast sea ice, lake ice.); 2- deposits on the ice-shelf and related forms ( supraglacial debris, ice cored moraines, dirt cones, erratic boulders, perched blocks, sinking stones, salt cones.); 3) rocks outcrops (mapped mainly according to their geomorphological response) and deposits (tills are differentiated according to their age); 4-hydrography (meltwater streams; meltwater lakes.); 5- epiglacial morphological features :due to ice dynamics (ice cliff, ice ramp, foliation patterns, main crevasses, pressure ridges) and due to wind and snow dynamics ( snowdrifts, snow barchans, sastrugis, wind scoop); 6-landforms and deposits derived from different processes (structural, glacial, periglacial, aeolian, gravity, weathering, coastal and marine); 7-available surveys and other data (geochronological datings, ice drillings, geophysicsal surveys, position and height of ice shelf front;, GPS measurement) The map, which is descriptive in many aspects, is designed as a key support for the interpretation of the dynamical behavior of the Ice Shelf and of the glacial evolution of the relief and the coastal area.